Game elements improve performance in a working memory training task - Manuel Ninaus; Gonçalo Pereira; René Stefitz; Rui Prada; Ana Paiva; Christa Neuper; Guilherme Wood (Serious Games Society, 2015)
The utilization of game elements in a non-game context is currently used in a vast range of different domains. However, research on game elements' effects in cognitive tasks is still sparse. Thus, in this study we implemented three game elements, namely, progress bar, level indicator, and a thematic setting, in a working memory training task. We evaluated the impact of game elements on user performance and perceived state of flow when compared to a conventional version of the task. Participants interacting with game elements showed higher scores in the working memory training task than participants from a control group who completed the working memory training task without the game elements. Moreover, game elements facilitated the individuals' performance closer to their maximum working memory capacity. Finally, the perceived flow did not differ between the two groups, which indicates that game elements can induce better performance without changing the perception of being "in the zone", that is without an increase in anxiety or boredom. This empirical study indicates that certain game elements can improve the performance and efficiency in a working memory task by increasing users' ability and willingness to train at their optimal performance level.